Knowledge and behavior towards COVID-19 in the northern region of the state of Rio de Janeiro – Brazil - Andre L Vargas; Larissa PV Souza; Lauryne MBR Paes; Raleigh P Dias; Thiago F Marotti; Thais Louvain de Souza; Inez Barcellos de Andrade (Journal of Infection in Developing Countries)
Introduction: Despite efforts by health organizations to share evidence-based information, fake news hindered the promotion of social distancing and vaccination during the coronavirus disease 2019 (COVID-19) pandemic. This study analyzed COVID-19 knowledge and practices in a vulnerable area in northern Rio de Janeiro, acknowledging the influence of the complex social and economic landscape on public health perceptions.